The efficiency of systemic solutions for the removal of asbestos in Poland: Current status and prospects - Anna Bernaciak; Arnold Bernaciak (Economic and Environmental Studies (E&ES), 2016)
The article summarizes the diagnosis of the impact of socio-economic factors on the rate of removal of asbestos in Poland. It presents the basic statistics on the rate of accumulation and removal of asbestos from the territory of the country and an attempt to identify the causes of common patterns in this area. It presents the most important information relating to systemic solutions in the field of asbestos removal. Moreover, the assessment of the effectiveness of functioning of the system has been discussed. Consequently, insufficient progress of implementation of national strategies and the low efficiency of system solutions in this area has been shown.
Keywords: R10; Q53; Q58; 330; asbestos; asbestos removal; regional dimension; Poland